Indonesia's Potential Trade Flow to EAEU Countries: The Gravity Model Approach - Ristanto, Didi (Gorontalo State University, 2024)
This research aims to examine the Indonesia's potential trade flow to EAEU countries using Augmented Gravity Model with Pseudo Poisson Maximum Likelihood (PPML) estimator, revealed comparative advantage (RCA) index, and constant market share analysis (CMSA) index on trade flows data for the period 2002-2022. The results indicates that trade relation between Indonesia and EAEU countries align with Heckscher-Ohlin Theory of trade, which states that dissimilar countries tend to trade more. Furthermore, the finding emphasizes the importance of Indonesia-EAEU preferential trade agreement to reduce or eliminate tariffs which otherwise will increase trade between both parties.